Does exposure to aflatoxin constrain efforts to reduce stunting in Zambia? - Ismail, S.; Shindano, J.; Nyirenda, D.B.; Bandyopadhyay, Ranajit; Akello, J. (Institute of Development Studies, 2014)
On 8 June 2013, the Vice President of Zambia stated that his government ‘is fully committed to reducing chronic undernutrition by 50 per cent in the next ten years…’ What are the challenges to meeting this goal? Zambia has both a high consumption of groundnuts and high levels of aflatoxin contamination of this commodity. Recent studies indicate an association between stunting and aflatoxin exposure. If the association exists, then Zambia faces serious challenges to reaching its target of 50 per cent reduction in chronic undernutrition. Recent efforts to identify atoxigenic strains for biocontrol in maize and groundnuts give cause for cautious optimism. Nonetheless, the challenges ahead demand both a high level of political will to achieve effective multisectoral collaboration and the willingness of the agricultural and health sectors to undertake rigorous monitoring of aflatoxin contamination and growth of young children, as well as the agricultural sector’s commitment to reduce substantially levels of aflatoxin contamination and to promote agricultural diversification.